Genetic polymorphism of candidate genes in pig meat production - Lieskovská, Zuzana; Kováčik, Anton; Trakovická, Anna (Acta Agraria Debreceniensis, 2011)
H-FABP, LEPR and MC5R genes were suggested as candidate genes for fat content in pig meat. The aim of this study was to detect genetic variation in the porcine H-FABP, LEPR and MC5R genes by PCR-RFLP method in a group of pigs. Genotyping of pigs was done by PCRRFLP methods. We identified three genotypes in the set of pigs, HH (0.504), Hh (0.412) and hh (0.084) for H-FABP (HinfI). Allele H showed higher frequency than allele h (0.710 vs. 0.290). Three genotypes were identified for the H-FABP (HaeIII) gene (DD - 0.194, Dd - 0.494, dd - 0.312). The allele D (0.441) showed slightly lower frequency than allele d (0.559). All three genotypes were identified for LEPR (HpaII) in the group of pigs (AA – 0.137, AB - 0.314, BB – 0.549). Higher frequency of LEPR gene was confirmed for allele B (0.706), as compared with allele A (0.294). We identified two genotypes for MC5R (BsaHI) in the group of pigs (AA - 0.348 and AG - 0.652), genotype GG was not found. As conforms with genotype structure, we recognize a higher frequency of allele A (0.674) as compared with allele G (0.326).